(untitled) (Research, Society and Development, 2020)
Specific Hypertensive Pregnancy Disease (DHEG) is one of the hypertensive syndromes and the most frequent complication in pregnancy, being the first cause of maternal mortality. The study is justified by the need for health professionals to know the various pathologies that affect women during pregnancy and, in particular, DHEG, which is considered one of the main public health problems. Knowledge of this information is essential to reduce maternal and fetal morbidity and mortality statistics, since this is the pathology with the highest incidence among pregnant women. Using as a guiding question: How does nursing care for women with specific hypertensive disease during pregnancy? Objectives: to understand through the bibliographic survey the knowledge of the nursing staff about the care directed to pregnant women with arterial hypertension and to identify the nursing knowledge about the possible complications of this pregnant woman. Methodology: This is a literature search with a qualitative approach. Results: DHEG is an important obstetric complication, the nurse must be responsible for providing the means for self-care with health and adherence to planned assistance in order to avoid it. We conclude that prenatal care, when performed correctly, and the training of professional nurses, enable the early identification of DHEG, allowing preventive measures and adequate treatment to be carried out, to reduce complications and improve the quality of life of mother and fetus.